Hybrid material of sustainable newspaper waste-derived cellulose for histamine sensing in kombucha tea - Pongpat Sukhavattanakul; Nadnudda Rodthongkum; Sarute Ummartyotin (Food Chemistry: X)
This study introduces a novel approach for sensing histamine by developing sensors from cellulose-based newspaper waste. The cellulose-based sensors, featuring diamine oxidase (DAO) as the sensing agent in cooperation with horseradish peroxidase (HRP) and 3,3′,5,5′-tetramethylbenzidine (TMB) solutions, are designed and assembled for targeted histamine detection. Experimental results demonstrate the sensor's exceptional sensitivity, with the observed color change serving as a reliable indicator of histamine concentration. In the presence of peroxidase and H2O2, the hydroxypropyl methylcellulose (HPMC)/DAO-immobilized enzyme-hydrolyzed cellulose-based film sensor gets oxidized, resulting in a blue spot. The highest sensitivity to histamine (3.30 mg/mL) was exhibited by the 3 w/w % HPMC/DAO-immobilized enzyme-hydrolyzed cellulose-based film, which showed the lowest b* value (−8.85 ± 0.01). This study showcases the potential of these films as an effective and cost-efficient platform for histamine detection in fermented beverages, offering promising applications in food safety screening. Ultimately, the research underscores the environmental sustainability of the HPMC-based hybrid material.